MODELLING THE SECOND-ORDER SEISMOELECTRIC EFFECT - Gennadinik B.I.; Bobrovnikov L.Z.; Mel'nikov V.P. (My University, 1989)
There are two different models that can be used to estimate the second-order seismoelectric effect. The Frenkel model describes the propagation of elastic waves in a disperse macroscopically homogeneous medium. The Kormil'tsev-Khachay model can be considered to be a microscopic model, it analyzes the percolation potential of an individual capillary, independently of the problem of propagation of elastic waves in the macroscopic medium. Both models neglect the inhomogeneity of the capillary system that models the rock medium. In the present work the authors analyze a model which combines the above-mentioned two in the sense that the size of the elementary volume of the rock over which the properties are averaged for purposes of evaluating the elastic wave propagation are of the order of the length of that wave, while the percolation potential that produces the second-order seismoelectric effect is assumed to be controlled by the behavior of uniform pores which are one to three orders of magnitude shorter than the wavelength.